2012
DOI: 10.1037/a0028297
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in emotional reactivity, regulation, and rejection sensitivity in adolescence.

Abstract: Although adolescents’ emotional lives are thought to be more turbulent than those of adults, it is unknown whether this difference is attributable to developmental changes in emotional reactivity or emotion regulation. Study 1 addressed this question by presenting healthy individuals aged 10–23 with negative and neutral pictures and asking them to respond naturally or use cognitive reappraisal to down-regulate their responses on a trial-by-trial basis. Results indicated that age exerted both linear and quadrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
381
4
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 393 publications
(409 citation statements)
references
References 100 publications
18
381
4
6
Order By: Relevance
“…Yet, even sophisticated models do not include affect-biased attention within the taxonomy of regulatory processes. Rather, such attention is typically described as a symptom of reactive 'bottom-up' emotional response (e.g., [11,12]). …”
mentioning
confidence: 99%
“…Yet, even sophisticated models do not include affect-biased attention within the taxonomy of regulatory processes. Rather, such attention is typically described as a symptom of reactive 'bottom-up' emotional response (e.g., [11,12]). …”
mentioning
confidence: 99%
“…concepts, processes and influences al., 2014; Silvers McRae, Gabrieli, Gross, Remy, & Ochsner, 2012;Steinberg, 2008;Thompson et al, 2013;Van der Graaff, Branje, De Wied, Hawk, Van Lier, & Meeus, 2014;Zeman et al, 2006). Recent neuroimaging studies in adolescents between 11 and 19 years of age have confirmed that, when observed by peers, young adolescents show a weaker activation of brain areas associated with cognitive control and instead show higher neuronal activity in regions associated with rewards, which explains the youngsters' need to actively seek acceptance of their social group (Brodbeck et al, 2013;Chein et al, 2011;Guyer et al, 2014;Steinberg, 2008).…”
Section: -8 Yearsmentioning
confidence: 92%
“…Reappraisal capacity was assessed using a computerized paradigm adapted from prior reappraisal protocols Silvers et al, 2012;Silvers, Weber, Wager, & Ochsner, 2015). We chose to employ a reinterpretation variant of reappraisal in the current study because of its applied relevance.…”
Section: Methodsmentioning
confidence: 99%